The cultural meaning of the category of modality in English and Uzbek fairy tales - Sattorova, Shahlo (The Lingua Spectrum, 2025)
In world linguistics, a great deal of scientific research has been conducted in the field of studying and investigating the category of modality. It is of great importance to study the psycholinguistic and extralinguistic reasons that give rise to this linguistic concept, their specific aspects in various aspects, especially in the comparative aspect of the non-related English and Uzbek languages. This article contains information about the development of the category of modality as a universal category and sheds light on the place of the category of modality in the relationship between culture and language, as well as the ways of expressing linguistic culture in fairy tales.